Spectroscopic investigations of Er2O3 doped silica borotellurite glasses - Aliyu, Umar Sa'ad; Mohamed Kamari, Halimah; Geidam, Ibrahim Gana; Alade, Ibrahim Olanrewaju; Noorazlan, Azlan Muhammad; Hamza, Abdulkarim Muhammad; Ahmad, Ahmad Fahad (Elsevier BV, 2021)
Er2O3 doped silica borotellurite glasses were synthesized using the melt-quenching technique with a chemical compositional formula (1 – x){(SiO2)0.2 [(B2O3)0.3 (TeO2)0.7]0.8} (Er2O3)x. Using the XRD, FTIR, UV–Vis, and photoluminescence spectroscopies, the structural, optical and spectroscopic properties of the glasses were studied. The absorption spectra and the refractive index, penetration depth, extinction coefficient, absorption coefficient, dielectric constant, optical conductivity for the glasses were presented. The absorption and emission cross-sections, cross-sectional gain, effective bandwidth, and bandwidth quality factor were also calculated using the UV–Vis data. Photoluminescence and the upconversion luminescence of the glasses were presented for pump wavelengths of 350 nm and 540 nm respectively. The studied glasses presented a high refractive index with values between 2.452 and 2.5153. The emission cross-section, effective bandwidth, bandwidth quality factor increased respectively from 3.53 × 10–22 to 1.3637 × 10–20 cm2, 66.3–103 nm, and 3.636 × 1028–91.095 × 1028 cm3 with increase in the Er3+ ions concentration in the glass system. The synthesized glasses exhibits a high-quality up-conversion emissions around 397.5 nm, 426 nm, and 475 nm from an excitation due to a pump of 540 nm wavelength. Furthermore, a high-quality luminescence emission around 543 nm, 500 nm, 475 nm and 425 nm from an excitation due to a pump of 350 nm wavelength was observed. Considering the values of the glasses refractive index, dielectric behaviour, absorption and emission cross-sections, effective bandwidths and other parameters presented, the synthesized glasses possess great potential for optoelectronic, laser and Erbium dope fibre amplifier (EDFA) applications.